Biogas Production from Combined Irish Potato and Poultry Wastes: Optimization and Kinetic Studies - M. Ibrahim, Umar; I. Ahmed, Saeed; Gutti, Babagana; M. Muhammad, Idris; D. Hamza, Usman; D. Ibrahim, Mustapha (International Journal of Engineering and Technology, 2018)
The combination of Irish potato waste (IPW) and poultry waste (PW) can form a synergy resulting into an effective substrate for a better biogas production due to some materials they contain. In this work, optimization and kinetic study of biogas production from anaerobic digestion of IPW and PW was investigated. Response surface methodology (RSM) was applied to optimize conditions such as initial pH, solids concentrations and waste ratios. The anaerobic digestion of the two wastes was carried out in the mesophilic condition and Box-Behnken design (BBD) was used to develop and analyze a predictive model which describes the biogas yield. The results revealed that there is a good fit between the experimental and the predicted biogas yield as revealed by the coefficient of determination (R2) value of 97.93%. Optimization using quadratic RSM predicts biogas yield of 19.75% at the optimal conditions of initial pH value 7.28, solids concentration (w/v) 9.85% and waste ratio (IPW:PW) 45:55%. The reaction was observed to have followed a first order kinetics having R2 and relative squared error (RSE) values of 90.61 and 9.63% respectively. Kinetic parameters, such as rate constant and half-life of the biogas yield were evaluated at optimum conditions to be 0.0392 day-1 and 17.68 days respectively. The optimum conditions and kinetic parameters generated from this research can be used to design real bio-digesters, monitor substrate concentrations, simulate biochemical processes and predict performance of bio-digesters using IPW and PW as substrate.Â Â